2008
DOI: 10.1093/rpd/ncn237
|View full text |Cite
|
Sign up to set email alerts
|

Patient dose in neonatal units

Abstract: Lung disease represents one of the most life-threatening conditions in prematurely born children. In the evaluation of the neonatal chest, the primary and most important diagnostic study is therefore the chest radiograph. Since prematurely born children are very sensitive to radiation, those radiographs may lead to a significant radiation detriment. Hence, knowledge of the patient dose is necessary to justify the exposures. A study to assess the patient doses was started at the neonatal intensive care unit (NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 5 publications
2
19
0
3
Order By: Relevance
“…Because of their size, more body tissues may be irradiated than larger children or adults (5). The risk of cancer induction per unit of dose is believed to be 2-3 times higher than that of the average population and 6-9 times higher than the risk from an exposure of a 60-yearold (6). Diagnostic radiology examinations need to be optimized so that doses received by the patient are not higher than needed to obtain the required diagnostic information.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their size, more body tissues may be irradiated than larger children or adults (5). The risk of cancer induction per unit of dose is believed to be 2-3 times higher than that of the average population and 6-9 times higher than the risk from an exposure of a 60-yearold (6). Diagnostic radiology examinations need to be optimized so that doses received by the patient are not higher than needed to obtain the required diagnostic information.…”
Section: Introductionmentioning
confidence: 99%
“…By limiting our sample to term deliveries between 37 and 43 wk gestation and restricting the period of exposure up to 2 d before a woman's date of delivery, we improved the accuracy of our determination of the timing of exposure to radiodiagnostic testing. At the same time, our findings may not apply to preterm infants, who both have higher rates of congenital and chromosomal anomalies, as well as major radiodiagnostic testing soon after birth (Table S3) [21],[22].…”
Section: Discussionmentioning
confidence: 83%
“…We included maternal-infant pairs comprising term liveborn infants who survived more than 30 d after date of birth. For three reasons, we restricted the sample to term infants ≥37 wk gestation, and who weighed at least 2,500 g at birth: First, preterm infants are commonly exposed to radiodiagnostic imaging procedures in hospital [21],[22], which could potentially contaminate the studied effect of prenatal exposure. Second, since term infants represent 94% of all livebirths [23], our findings would remain applicable to most pregnancies.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to our findings, in a study by Smans et al, neonatal weight has been divided into three groups (less than 1,000 g, 1,000 up to 2,500 g and over 2,500 g). They observed that with the increase in weight, an average of ESD also is increased [15]. …”
Section: Discussionmentioning
confidence: 99%